Evaluation of the applicability of the current CDC pediatric ventilator-associated events (PedVAE) surveillance definition in the neonatal intensive care unit population - Novisi Arthur; Ishminder Kaur; Alison J. Carey (BMC, 2022)
Abstract Background There is limited data on pediatric ventilator-associated events (PedVAE) in the neonatal intensive care unit (NICU) setting, since the CDC mandated state reporting of these events in January 2019. This study sought to describe PedVAE rates and characteristics in the NICU population. Methods Single-center case-control study of infants requiring mechanical ventilation in a 39-bed level IV NICU between January 1, 2018 and December 31, 2020. Baseline infant demographic, respiratory support and antibiotic use data was obtained and comparisons were performed between patients with potential PedVAEs and those without events. Result Two hundred and nine infants were mechanically ventilated. Two of the 126 patients ventilated for ≥4 days met CDC criteria for PedVAEs with a total of 3 events, and 32 (25%) received antibiotics with escalation of respiratory support, primarily for tracheitis. Conclusion NICU-specific data on PedVAE is limited. Only 2 infants in the study period met the current CDC criteria for PedVAE with a rate of 0.9 events per 1000 ventilator days. The current CDC PedVAE definition might be inadequate to identify actionable VAEs to inform prevention efforts in the NICU population, and alternate indices could better characterize these events.